Why Fujitsu is developing the scoring gymnastics? - Suzuki, S. (Applied Innovation Research - New Businesses Creation Initiatives : Fujitsu World Tour 2017 - Human Centric Innovation Driving Digital Transformation, 2017)
Challenging tasks with scoring gymnastics - ERecognition of complicated and high-speed movement - Adaptation to fast-changing repertory of its techniques - Securing fairness of its scoring